Corporate governance literature review there is a financial performance perspective - Yogi Ginanjar; Amelia Setiawan (Institute of Computer Science (IOCS), 2023)
The purpose of this research is to identify the factors that influence good corporate governance (GCG). GCG is a representation of the relationship between parties that influence the direction of the company and financial performance. Basically, to understand how much influence GCG has on company performance, we need to apply agency theory. This study will use a literature review methodology to examine and explore documents related to GCG, particularly the impact of GCG on financial performance. The data used in this study is second party data. GCG implementation should have a positive impact on company performance, but in practice, many companies did not implement GCG. Most companies only implement government regulations without studying the role and function of GCG itself. The urgency of this research is to implement GCG on company performance by implementing it and studying the role and function of GCG itself